The impact of colonialism on policy and knowledge production in International Relations. (10th January 2022) - Gani, Jasmine K; Marshall, Jenna
Abstract : In the introduction to this special issue, guest-editors Gani and Marshall argue that we must uncover the legacy of race, colonialism and imperialism in International Relations. They problematize the academic–practitioner relationship, asking how this racialized knowledge exchange has influenced theory and policy in IR. Abstract: Is there an academic–policy divide, and does that gap need to be bridged? For decades, International Relations (IR) scholars have reflected on their roles and responsibilities towards the 'real world', while policy-makers have often critiqued the detachment of academic research. In response, there have been increased calls for academics to descend from their 'ivory tower'. However, the articles in this 100th anniversary special issue of International Affairs interrogate this so-called theory–policy divide and problematize the exchange of knowledge between academics and practitioners, highlighting the colonial underpinnings of their historical entanglements. In this introductory article we bring together the core arguments of the special issue contributions to delineate three prominent dynamics in the academic–practitioner nexus: the role of academia as a supplier of knowledge for colonial policies; the influence of imperial practice and policy-makers in shaping IR and academic knowledge production; and the contestation from academics and/or practitioners against racial hierarchies in knowledge production and policy-making. Confronting the exclusions, amnesias and denials of colonialism in the theory and practice of International Relations is the necessary first step in any process of repair towards a more just and viable politics.